Masked hypoglycemia in pregnancy - Naik, Dukhabandhu; Hesarghatta Shyamasunder, Asha; Doddabelavangala Mruthyunjaya, Mahesh; Gupta Patil, Rita; Paul, Thomas Vizhalil; Christina, Flory; Inbakumari, Mercy; Jose, Ruby; Lionel, Jessie; Regi, Annie; Jeyaseelan, P. Visalakshi; Thomas, Nihal (Journal of diabetes, 2017)
Background Hypoglycemia is a major hindrance for optimal glycemic control in women with gestational diabetes mellitus (GDM) on insulin. In the present study, masked hypoglycemia (glucose <2.77mmol/L for ≥30 min) was estimated in pregnant women using a continuous glucose monitoring (CGM) system. Methods Twenty pregnant women with GDM on insulin (cases) and 10 age‐matched euglycemic pregnant women (controls) between 24 and 36 weeks gestation were recruited. Both groups performed self‐monitoring of blood glucose (SMBG) and underwent CGM for 72 h to assess masked hypoglycemia. Masked hypoglycemic episodes were further stratified into two groups based on interstitial glucose (2.28–2.77 and ≤2.22 mmol/L). Results Masked hypoglycemia was recorded in 35% (7/20) of cases and 40% (4/10) of controls using CGM, with an average of 1.28 and 1.25 episodes per subject, respectively. Time spent at glucose levels between 2.28 and 2.77 mmol/L did not differ between the two groups (mean 114 vs 90 min; P = 0.617), but cases spent a longer time with glucose ≤2.2 mmol/L. Babies born to women with GDM were significantly lighter than those born to controls (2860 vs 3290 g; P = 0.012). There was no significant difference in birth weight within the groups among babies born to women with or without hypoglycemia. Conclusion Euglycemic pregnant women and those with GDM on insulin had masked hypoglycemia. Masked hypoglycemia was not associated with adverse maternal or fetal outcomes. Therefore, low glucose levels in the hypoglycemic range may represent a physiologic adaptation in pregnancy. This response is exaggerated in women with GDM on insulin. 背景 对于使用胰岛素治疗的妊娠糖尿病(gestational diabetes mellitus,GDM)妇女来说,低血糖是她们获得最佳血糖控制的主要障碍。在当前这项研究中,使用动态血糖监测(continuous glucose monitoring,CGM)系统来评估孕妇的隐性低血糖(血糖< 2.77 mmol/L,持续时间≥ 30分钟)。 方法 本研究招募了20名使用胰岛素治疗的GDM孕妇(病例组)以及10名年龄相匹配的血糖正常的孕妇(对照组),她们的孕周为24至36周。为了评估隐性低血糖,两组孕妇都要进行自我血糖监测,并且还要进行72小时的CGM。根据组织间液的葡萄糖值将隐性低血糖事件进一步分为两组(2.28‐2.77 mmol/L与≤ 2.22 mmol/L)。 结果 使用CGM后发现在病例组中有35%(7/20)记录到了隐性低血糖,而在对照组中有40%(4/10)记录到了隐性低血糖,两组中每名受试者的平均低血糖事件分别为1.28与1.25次。两组中葡萄糖水平介于2.28与2.77 mmol/L之间的持续时间没有显著性差异(平均持续时间分别为114与90分钟;P = 0.617),但是病例组葡萄糖水平≤ 2.2 mmol/L的持续时间更长。GDM妇女所产婴儿的体重要显著低于对照组所产婴儿的体重(分别为2860 g与3290 g;P = 0.012)。无论孕妇是否有低血糖她们所产婴儿的出生体重之间都没有显著性差异。 结论 血糖正常的孕妇以及使用胰岛素治疗的GDM妇女都有隐性低血糖。隐性低血糖与母体或者胎儿不良结果之间没有相关性。因此,在这个范围内的低血糖水平可能是妊娠期的生理适应反应,对于使用胰岛素治疗的GDM妇女来说这种反应被进一步扩大了。 Continuous glucose monitoring profiles in women with gestational diabetes mellitus on insulin (a) with or (b) without masked hypoglycemia. Graphs show glucose profiles in individual women over 72 h. (a) In women with GDM and masked hypoglycemia, the episodes of masked hypoglycemic occurred mostly during the night (2300–0600 h), corresponding to values numbered 124–230, 432–518, and 720–820 (on the first, second and third nights, respectively). (b) In women with GDM but no masked hypoglycemia, there was a trend towards lower glucose values at night (2300–0600 h), corresponding to values numbered 124–230, 432–518, and 720–820, but these values were above 2.77 mmol/L (50 mg/dL). Highlights Glucose dynamics in pregnancy are altered, with a trend towards lower fasting levels in the hypoglycemic range. Euglycemic pregnant women, as well as those with gestational diabetes mellitus on insulin, experienced masked hypoglycemia, which may be a physiologic adaptation in pregnancy. Hypoglycemic episodes did not adversely affect maternal or fetal outcomes. Continuous glucose monitoring uncovered masked hypoglycemia in pregnancy. This was not associated with adverse maternal or fetal outcomes, indicating that low glucose may be a physiologic adaptation.